Prospective validation study of the International Classification of Functioning, Disability and Health score in Crohn's disease and ulcerative colitis. (1st October 2014) - Leong, Rupert W.L.; Huang, Tony; Ko, Yanna; Jeon, Ari; Chang, Jeff; Kohler, Friedbert; Kariyawasam, Viraj
Abstract: Background and aims: Inflammatory bowel diseases (IBD) may result in disability. We aim to validate a novel scoring system for the IBD disability index (IBD-DI), and identify predictors of disability and its correlation with work absenteeism. Methods: This prospective IBD ambulatory clinic cohort study measured IBD-DI, Crohn's Disease Activity Index (CDAI) for Crohn's disease (CD) or partial Mayo score (pMayo) for ulcerative colitis (UC), IBDQ quality-of-life, and Work Productivity and Activity Impairment. Negative IBD-DI represented greater disability. Validation tests were performed and predictors and extent of work absenteeism were determined. Results: 166 consecutive subjects were recruited (75 CD, 41 UC, 50 controls). IBD-DI correlated with CDAI (r = -0.77, P < 0.001), pMayo (r = -0.82, P < 0.001) and IBDQ (r = 0.86, P < 0.001). IBD-DI differentiated CD, and UC from controls (medians -7, -4, +10; P < 0.001) with a score of N3.5 identifying controls with 94% sensitivity and 83% specificity (area-under-curve 0.92). Stable patients had unchanged IBD-DI (P = ns) but not in those who relapsed (P < 0.001). Intraclass correlation was 0.89 and Cronbach's alpha of internal consistency was 0.94. Diagnosis age, sex, phenotype, perianal disease, prior surgery, steroid-use and disease duration did not influence the IBD-DI but active use of biological agents significantly reduced disability (P = 0.03). 21.6% of IBD patients had moderate-severe disability equating to missing >25% of work hours in the previous week. Multivariate analysis identified that only IBD-DI to be predictive of unemployment status (OR: 0.94; 95% CI: 0.89–0.99). Conclusions : The IBD-DI is a valid tool measuring disability in both CD and UC and correlates with workforce participation. It is a potential useful tool in the assessment of participation restriction and activity limitation. Trial registration: ACTRN12613000903785.